TYPOLOGY OF GENDER-MARKED PHRASEOLOGISMS IN CROSS-CULTURAL COMPARISON - Viktoria Gofurova (Western European Studies, 2026)
The present article investigates gender-marked phraseologisms from a cross-cultural perspective, with the aim of developing a typology based on their semantic, conceptual, and axiological characteristics. Phraseological units are examined as culturally conditioned linguistic signs that encode collective representations of masculinity and femininity (Dobrovol’skij & Piirainen, 2005; Sabban, 2008). The material is drawn from several linguocultural traditions and includes idioms containing explicit gender markers as well as units with implicit gender reference. Using semantic and comparative analysis, the study identifies major typological groups of gender-marked phraseologisms and demonstrates both universal tendencies and culture-specific patterns in the linguistic conceptualization of gender (Hellinger & Bußmann, 2001–2003; Wierzbicka, 1997). The findings reveal that while many cultures share common metaphorical models of masculinity and femininity, their evaluative orientation and functional distribution differ significantly across languages
Keywords: phraseology; gender linguistics